2021
DOI: 10.1590/1414-431x2021e11363
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of KIF14 regulates the cell cycle and predicts poor prognosis in cervical cancer: a study based on integrated approaches

Abstract: Cervical cancer (CC) is the most common malignant tumor in females. Although persistent high-risk human papillomavirus (HPV) infection is a leading factor that causes CC, few women with HPV infection develop CC. Therefore, many mechanisms remain to be explored, such as aberrant expression of oncogenes and tumor suppressor genes. To identify promising prognostic factors and interpret the relevant mechanisms of CC, the RNA sequencing profile of CC was downloaded from the Cancer Genome Atlas and the Gene Expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In addition, KIF14 was upregulated in tumor tissues and could predict unfavorable outcomes in patients with ovarian cancer (29). These aforementioned studies indicated that in numerous types of cancer, KIF14 might be a promoter of cancer progression, and could be a potential biomarker for prognosis (21,(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, KIF14 was upregulated in tumor tissues and could predict unfavorable outcomes in patients with ovarian cancer (29). These aforementioned studies indicated that in numerous types of cancer, KIF14 might be a promoter of cancer progression, and could be a potential biomarker for prognosis (21,(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 96%
“…As a crucial member of the kinesin family, KIF14 has been reported to be a regulator of tumor development and progression in previous studies and could also be a potential biomarker in the management of patients with cancer ( 24 , 25 ). A prior study revealed that KIF14 inhibition using small interfering (si)RNA could repress proliferation and enhance apoptosis in medulloblastoma cells, while KIF14 inhibition using short hairpin RNA could suppress cell viability, colony formation, invasion, migration and tumor sphere formation in medulloblastoma cells ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…HJURP is reported to be an oncogene that promotes cancer cell proliferation, migration, and invasion (Chen et al, 2018;Wei et al, 2019;Serafim et al, 2020;Lai et al, 2021). KIF14 is confirmed to promote cancer cell proliferation and contribute to chemoresistance (Singel et al, 2014;Xiao et al, 2021). Silencing TTK is also found to inhibit the proliferation and invasion and increase radiosensitivity and chemosensitivity of cancer cells (Chen S. et al, 2019;Huang et al, 2020;Zhang et al, 2021b;Qi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to the existing literature, CDK2 was a more promising therapeutic target for cervical cancer [ 37 , 59 ]. CHEK1 hub gene produced a high score expression value in CC tissues compared with normal tissues and was considered as a significant upregulated expressed gene (P < 0.01) [ 20 , 44 ].…”
Section: Discussionmentioning
confidence: 99%